Renascence lace and irish lace: production contexts in artisan associations of the northeast region of Brazil (ModaPalavra e-periódico, 2020)
The present study aims to identify the context of productionof Renaissance and Irish lace in the artisan associations of SãoJoão doTigre, Paraíba and Divina Pastora, in Sergipe. Thequalitative and descriptive research was used and the datacollection was done using bibliographical and field research,with the application of a semi-structured questionnaire. Theresearch sample is madeup of four entities, two associationsand one cooperative that produce Renaissance Income in thecity of São João do Tigre, in the State of Paraíba, and anassociation that produces Irish Income in the city of DivinaPastora, in the State of Sergipe. Through the study, it wasnoticed that each entity has a form of organization and thatits main challenges refer to the preservation of the techniquesand the commercialization of the products.
Keywords: renaissance lace; irish lace; crafts; association